Integration of coordination and kinetic analysis reveals mechanisms of upper limb joint loading and technique-specific strategies in female gymnastics - Brtva, P.; Mulloy, F.; Hamill, J.; Irwin, G.; Farana, R. (Sports Biomechanics, 2026)
This study aimed to identify differences in upper-limb coordination by integrating vector coding with joint kinetics across three round-off (RO) techniques to better explain potential injury mechanisms. Twelve female gymnasts performed six trials of each RO technique (Parallel, Reverse, T-shape). The kinematic and kinetic data were collected. All analyses focused on the contact phase of the second hand. Elbow and Wrist joint flexion/extension (EF/E-WF/E) and rotation (EROT-WROT) couplings were assessed using modified vector coding to determine coupling angle (CA) and variability (CAV). Elbow joint adduction/abduction moments (Melbow) and joint power (JPelbow) were calculated using inverse dynamics. Joint kinetics and CA were overlaid on the same plots to visualise how kinetic patterns corresponded with coordination dynamics. Results showed decreased Melbow using the T-shape technique (p < 0.001) with EROT-WROT in-phase, while Reverse and Parallel techniques exhibited anti-phase with increased Melbow (p < 0.001) and lower CAV using Reverse technique. Furthermore, EF/E-WF/E coupling revealed technique-specific control strategies; notably, the T-shape technique exhibited a different transition from anti-phase to in-phase motion, indicating a potentially more effective transfer from JPelbow absorption to generation. The result provides new insights into the underlying mechanism of these differences through integration of coordination analysis with traditional biomechanics.